2018
DOI: 10.4168/aair.2018.10.4.379
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Food Allergy-Related Quality of Life From Parents' Perception in Turkish Children

Abstract: PurposeFood allergy (FA) affects the daily lives of children and parents in varying degrees. The Food Allergy Quality of Life Questionnaire-Parent Form (FAQLQ-PF) is a valid and reliable instrument to assess the quality of life (QoL) of children from parents' perception. The aim of this study was to validate and determine the reliability of the Turkish FAQLQ-PF and to assess QoL in food-allergic children.MethodsChildren aged between 0 and 12 years and diagnosed with immunoglobulin E (IgE)-mediated FA for at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 18 publications
5
31
2
Order By: Relevance
“…Most children had been diagnosed by an allergist (15/24; 62.5%), had to avoid 1 to 2 foods (18/25; 72.0%), and nearly one-third (8/28; 28.6%) had a history of anaphylaxis. For mothers with children aged 0 to 1.5 years, the mean PASS score was 22.6 plus or minus 16 For mothers with children aged 1.5 to 8 years, the mean GAD-7 score was 7.2 plus or minus 6.0, with 33.8% of mothers reporting clinical anxiety (score of !10). Statistically significantly greater raw GAD-7 scores were found in cases (n ¼ 18; mean, 10.33 [95% CI, 6.23-7.74]) than controls (n ¼ 233; mean, 6.99 [95% CI, 6.23-7.74; P < .02]) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most children had been diagnosed by an allergist (15/24; 62.5%), had to avoid 1 to 2 foods (18/25; 72.0%), and nearly one-third (8/28; 28.6%) had a history of anaphylaxis. For mothers with children aged 0 to 1.5 years, the mean PASS score was 22.6 plus or minus 16 For mothers with children aged 1.5 to 8 years, the mean GAD-7 score was 7.2 plus or minus 6.0, with 33.8% of mothers reporting clinical anxiety (score of !10). Statistically significantly greater raw GAD-7 scores were found in cases (n ¼ 18; mean, 10.33 [95% CI, 6.23-7.74]) than controls (n ¼ 233; mean, 6.99 [95% CI, 6.23-7.74; P < .02]) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on food allergy have used a variety of anxiety and QoL tools 10 , 11 , 12 , 13 , 14 and used in diverse populations. 2 , 15 , 16 , 17 , 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature reported that food allergies are prevalent in this age group; thus, it is important to measure their QoL [6,8]. The FAQLQ-PF is widely utilized worldwide and has been adapted and translated into nine languages, including Spanish, Turkish, Swedish, Japanese, Portuguese, Dutch, French and Ukrainian [23][24][25][26][27][28][29][30]. It is a valid and reliable tool to assess the QoL of children with food allergies by using parents as a proxy to answer the questionnaire [22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports from our group and from others provide further evidence that children and adolescents with FHS have low HRQoL [ 25 , 26 , 27 , 28 , 29 ]. Children with more severe FHS, asthma comorbidity or experienced anaphylaxis have lower quality of life than those with less severe disease [ 30 , 31 , 32 ]. Among younger adolescents (ages 12–13 years), different phenotypes of FHS were shown to have no further impact on HRQoL, but tended to impact on those with a current food allergy [ 33 ].…”
Section: Introductionmentioning
confidence: 99%